SALURAN DAN MARGIN PEMASARAN KOPI CAP LERENG TANCAK KEMBAR DI DESA ANDUNGSARI KECAMATAN PAKEM KABUPATEN BONDOWOSO - Dinda Dara Ardila; Titin Agustina; Sri Subekti (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
Arabica and robusta coffees as the agricultural commodities are cultivated in Pakem sub-district, Bondowoso regency. One of the companies processing arabica and robusta coffees in Bondowoso is Lereng Tancak Kembar agroindustry. However, the agroindustry often experiences some obstacles to market its products because road access to the area is quite difficult, so the condition increases transportation costs. Therefore, it is necessary to know about the marketing channel of Lereng Tancak Kembar, so it affects the price and margin of coffee marketing to the last consumers. The reserach area was determined purposively. Descriptive data analysis was used to analyze the coffee marketing channel, and marketing margin analysis was used to know the coffee marketing margin. The findings indicated that: (1) the marketing of Lereng Tancak Kembar coffee had four marketing channels, consisting of two Arabica coffee marketing channels and two robusta coffee marketing channels. The first marketing channel of arabica coffee included: agroindustry - sales - retailers - consumers. The second marketing channel included: agroindustry - retailers - consumers. The first marketing channel of robusta coffee included: agro-industry - sales - retailers - consumers. The second marketing channels of robusta coffees included: agroindustry - retailers - consumers. (2) the marketing margin for the first channel of arabica coffee was Rp. 86,660.00, and the second channel was Rp. 53,330.00. The marketing margin for the first channel of robusta coffee was Rp. 100,000.00, and the second channel was Rp. 85,000.00.